Hubungan Tingkat Pengetahuan dengan Upaya Pencegahan Penyakit Glaukoma pada Klien Berisiko di Wilayah Kerja Puskesmas Jenggawah Kabupaten Jember - Siswoyo Siswoyo; Latifa Aini Susuma; Santi Rahayu (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Glaucoma was an eye disorder characterized by increased pressure on the eyeball, optic nerve opticatrophy and diminution of the visual field. Clients' knowledge towards glaucoma was important tohave such an early detection. It was done to avoid the blindness causes of glaucoma. The objectivesof this research were to analyze the correlation between knowledge with prevention efforts glaucomadisease in the area of Jenggawah clinical. This research was used in observational analytic designwith cross sectional approach. A total of 39 respondents obtained by purposive sampling technique.The data analysis that used was Spearman correlation test with significance level 0,05. The resultswas showed that the average value of knowledge level was 17.49 and the average at preventioneffort of glaucoma disease was 75.03. There was a significant relationship between the level ofknowledge with prevention efforts glaucoma disease (p value = 0.001, r = 0.600). There were astrong and positive correlation which means the higher in the level of knowledge that made a goodprevention of glaucoma disease. This study showed that the importance of providing knowledgeabout glaucoma disease to increase prevention of glaucoma disease in risky clientsKeywords: client is at risk, knowledge level, prevention of glaucoma disease